DEVELOPMENT OF OPTIMIZED COMPUTATIONAL MODEL FOR NON-STRUCTURAL MATERIAL BASED ON ENVIRONMENTAL MANAGEMENT SYSTEM - MOAYEDI, FARZANEH (2019)
Construction projects have major impacts on the environment and are considered as one of the major consumers of natural resources